Electrochemical grafting passivation of silicon via electron transfer at polymer/silicon hybrid interface. (1st September 2017) - Chen, Jianhui; Shen, Yanjiao; Guo, Jianxin; Chen, Bingbing; Fan, Jiandong; Li, Feng; Liu, Baoting; Liu, Haixu; Xu, Ying; Mai, Yaohua
Highlights: Si surface passivation by PEDOT:PSS thin film is dominated by PSS species. Passivation can be enhanced by light soaking and applied bias voltage. The passivation is an electrochemical oxidation/deoxidation process. The interface state is switchable, which can be controlled by electron transfer. A polymer-passivated both-sides Si heterojunction solar cell is developed. Abstract: The most important aspect in the development of Si-based photovoltaic technologies is the passivation of the Si wafer surface. Here, we show that Poly(3, 4-ethylthiophene):polystyrenesulfonate (PEDOT:PSS) thin films, frequently used in organic/inorganic hybrid solar cells as emitter layers, provide an excellent surface passivation with a millisecond (ms) level effective minority carrier lifetime ( τeff ). More importantly, we find that this passivation effect is dominated by the PSS species in PEDOT:PSS rather than PEDOT ones. The PSS thin film passivation yields a high τeff of 9.4 ms on a high-resistivity Si wafer. The interface nature of PSS/Si is unveiled by the X-ray photoelectron spectroscopy and first-principles total-energy calculations together. An electrochemical passivation mechanism is clarified: the Si sub-oxides form at PSS/Si interface by the electrochemical grafting O groups in PSS onto Si surface, which can be controlled by injecting holes or electrons into the Si surface, leading to a switchable interface state between oxidation and deoxidation. To examine the application of the passivation strategy in real devices, we develop a polymer-passivated both-sides Si heterojunction solar cell with light-induced enhancement of photovoltaic performances, which is consistent with the light-induced enhancement of τeff .